If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = 5 + n Solving -1 = 5 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -1 + -1n = 5 + n + -1n Combine like terms: n + -1n = 0 -1 + -1n = 5 + 0 -1 + -1n = 5 Add '1' to each side of the equation. -1 + 1 + -1n = 5 + 1 Combine like terms: -1 + 1 = 0 0 + -1n = 5 + 1 -1n = 5 + 1 Combine like terms: 5 + 1 = 6 -1n = 6 Divide each side by '-1'. n = -6 Simplifying n = -6
| 72=3x(x+2) | | 1.3q-3.8-5.6q=-5.3q-4.3 | | 130=10x+7y | | -14=-7m | | 4+9y-3=7y+43-4y | | 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a | | 18x-12=22x+8 | | 3k=-12 | | 8-5x=-22 | | 8-5x=-22 | | 12.5*n=100 | | 4x^3-9x^2-x-6=0 | | -21/4(-10) | | 31=-7+x | | -21/4(10) | | 2(x+22)=5+3(x-2)-4x | | -3x8+4/(-2) | | r-45=-45 | | 9g+11=-2 | | 4xy^2+44x^2y^2-28xy^2=0 | | 3/4w=-16/27 | | 3/4s=-16/27 | | -16t^2+16=0 | | ab-9a+4b-36= | | -5(-3u+7)-3u=6(u-6)-7 | | -3=k+2 | | 2/3(1/8+4x)-3/8=5/8 |